Two manuscript messages: 1. Difference between Plural and Collective Noun and the Noun for Ibn Al-Nathem 2. The adverb coupled with Maybe for Amir Badshah: Investigation Study - Rabaya, Marwan Mustafa (Journal of Humanities & Social Sciences, 2021)
This study aims to investigate two manuscript texts on some syntactical and morphological issues, which are “The difference between the plural, collective noun and the gendered noun” by Ibn al-Nazim, and the second the adverb which is connected with"Qad’ by Amir Badshah. Those twoscholars left many precious scientific works. The researcher found these issues deserve to be published since they consider as one of the main issues that had been discussed by the scholars with their students during lessons. These issues did not reach the size of huge classifications, but it is one or two issues where the classified book express its opinion in concise and focus, which is considered of fruitful and great benefits in language research and the intellectual activity in general, and they were not attainable and accessible, particularly in obtaining second copies of those letters. Accordingly, in order not to remain a buried treasure waiting for someone to discover or get it out to the light, the researcher has obtained one letter with two different versions from two different places; and the other one is a unique copy where the researcher followed the scientific methodology in its publication and verification.
Keywords: Achievement of Manuscript Letters; Ibn Al-Nazim; Collection; Amir Badshah; Qad; Al-Hal